Assessment of Suicidal Cases Among Emergency Department Applicants Kütahya Evliya Çelebi Training and Research Hospital Experience - Emine Kadioğlu (Eurasian Journal of Emergency Medicine, 2020)

(untitled)
Aim:Our work is aim at sharing our experiences in suicide cases which constitute a significant part of the psychiatric emergency cases. We hope to draw attention to the factors involved in suicide attempts. This is intended to contribute to taking precautions and prevent suicide attempts by determining the possible risk factors.Materials and Methods:This study was conducted by retrospectively reviewing records of 292 cases filed at Dumlupınar University, Kütahya Training Research Hospital Emergency Service as suicide attempts between January 01 and December 31, 2016, in which the “Suicide Attempt Registration Form” was completed.Results:Suicide attempts were found to occur more frequently in females within the ages of 15-24 years, particularly in cases with family problems, psychiatric diseases, and problems with the opposite sex.Conclusion:In this study, we evaluated demographic and risk factors of suicide attempts in our hospital. Local government, non-governmental organizations, and health service providers need to cooperate in developing policies which seeks to prevent suicidal behavior. In addition, because psychiatric diseases has an important place in the etiology of suicide attempts, it is important that these patients are followed up closely and that symptoms indicative of suicide are treated and an absolute psychiatric evaluation and follow-up be done before discharge of the emergency patients.